Mapping And Analysis of Environmental Risk Factors Leptospirosis Incidence Based Geographic Information System (GIS) In Sampang Regency - Annisa Rahim; Ririh Yudhastuti (Universitas Airlangga, 2015)
Abstract: One of the zoonosis in Indonesia is leptospirosis. Leptospirosis is caused due to infection of bacteria Leptospira. There were 107 cases and 9 deaths due to leptospirosis in Sampang. The incidence of leptospirosis in Sampang was an outbreak. The purpose of this study was to map the distribution of leptospirosis cases in Sampang in 2013 and to analyze environmental risk factors of leptospirosis cases (rainfall, altitude, and the presence of flood). This study was an observational-descriptive study and used cross-sectional study design. The unit of analysis of the study was administrative regions based on the districts. There was patients of leptospirosis in 4 districts in Sampang regency, there are Sampang district, Camplong district Robatal district and Omben district. The highest incidence of leptospirosis in Sampang regency was occured in Sampang district with rainfall more than 177.6 mm, altitude less than 47mdpl, and had experienced flooding. Mapping the incidence of leptospirosis showed the distribution of leptospirosis cases tend to be concentrated in Sampang district which had a history of flooding status. The conclusion is rainfall, altitude, and presence of flood are risk factors of leptospirosis. The advice is to improve surveillance of patients with leptospirosis particularly during floods, to do outreach to the community, to perform cross-sector cooperation, to avoid or to reduce the frequency of direct contact with the flood to minimize transmission of leptospirosis.Keywords: leptospirosis incidence, risk factors, mapping